First report on the gastropod proapoptotic AIF3 counterpart from disk abalone (Haliotis discus discus) deciphering its transcriptional modulation by induced pathogenic stress - Elvitigala, D. A. S..; Jayasooriya, R. G. P. T; Whang, I; Lee, J. (Elsevier, 2015)
Apoptosis inducing factor (AIF) is a flavoprotein that is involved in oxidative phosphorylation and induces apoptosis in eukaryotic cells. There are three isozymes of AIF that have been identified to date, designated as AIF1, AIF2, and AIF3; the human AIF3 is also known as an AIF-like protein (AIFL). This study aimed to identify and characterize a homologue of AIF3 from disk abalone (AbAIF3) that belongs to the phylum Mollusca. The open reading frame (ORF) of AbAIF3 is 1749 base pairs (bp) in length and encodes a protein of 583 amino acids, with a predicted molecular mass of 63.14 kDa. Based on our in-silico analysis, the AbAIF3 protein harbored the typical domain architecture as that of the known AIF family proteins, consisting of N-terminal Rieske and pyridine nucleotide-disulphide oxidoreductase domain. Comparative protein sequence analysis confirmed that AbAIF3 is a homolog of AIF3. Moreover, our phylogenetic analysis revealed that AbAIF3 had a close evolutionary relationship with the molluscan counterparts. Interestingly, AbAIF3 was shown to induce apoptosis in HEK293T cells using transfection assays followed by flow cytometric analysis. In addition, we found that AbAIF3 mRNA expression was ubiquitous in physiologically important tissues, and significantly modulated upon experimental immune stimulations in hemocytes. Collectively, our study illustrates the indispensable role of AbAIF3 in inducing apoptosis in disk abalones, which in turn might be involved in hosts' immune defense mechanisms against microbial infections.
Keywords: Disk abalone; Apoptosis inducing factor 3; Apoptotic activity; Immune stimulation; Transcriptional modulation